2020
DOI: 10.3390/ijms21186508
|View full text |Cite
|
Sign up to set email alerts
|

High Resolution Multimodal Photoacoustic Microscopy and Optical Coherence Tomography Visualization of Choroidal Vascular Occlusion

Abstract: Photoacoustic microscopy is a novel, non-ionizing, non-invasive imaging technology that evaluates tissue absorption of short-pulsed light through the sound waves emitted by the tissue and has numerous biomedical applications. In this study, a custom-built multimodal imaging system, including photoacoustic microscopy (PAM) and optical coherence tomography (OCT), has been developed to evaluate choroidal vascular occlusion (CVO). CVO was performed on three living rabbits using laser photocoagulation. Longitudinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…For applications in ophthalmology, PAM has been integrated with OCT, SLO, and fluorescence microscopy to combine the benefits of each imaging modality. These multimodality imaging systems have been extensively explored for identification of retinal vessels (RVs), choroidal vessels (CVs), retinal pigment epithelium (RPE) cells, melanin, corneal neovascularization, retinal neovascularization (RNV), , laser-induced injury, retinal vein occlusion, and choroidal neovascularization (CNV) in rodents ( e.g. , mice and rats) and large animal eyes ( e.g.…”
Section: Introductionmentioning
confidence: 99%
“…For applications in ophthalmology, PAM has been integrated with OCT, SLO, and fluorescence microscopy to combine the benefits of each imaging modality. These multimodality imaging systems have been extensively explored for identification of retinal vessels (RVs), choroidal vessels (CVs), retinal pigment epithelium (RPE) cells, melanin, corneal neovascularization, retinal neovascularization (RNV), , laser-induced injury, retinal vein occlusion, and choroidal neovascularization (CNV) in rodents ( e.g. , mice and rats) and large animal eyes ( e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Combining PAM with OCT imaging establishes complementary structural and vascular contrast, which has been used to capture neovascularization associated with DR and wet AMD in animal models (483)(484)(485)(486)(487). Nguyen et al further demonstrated that the multimodal combination of PAM with OCT has utility in monitoring vascular and structural changes associated with vascular occlusion (488,489). PAM has additionally been combined with Doppler OCT to measure retinal oxygen metabolism with the potential to aid in an earlier diagnosis of DR, AMD, and glaucoma (478,490).…”
Section: Multimodal Imagingmentioning
confidence: 99%
“…[255][256][257][258][259] Combined PAM and OCT has also shown advantages for visualizing vascular and structural changes associated with retinal vein occlusion (Figure 7) and choroidal vascular occlusion over FA. 260,261 Finally, PAM and OCT can be used to quantify Source: Reprinted with permission from Carrasco-Zevallos and colleagues 243 and Ehlers and colleagues. 249 4D, 4-dimensional; iOCT, intraoperative optical coherence tomography.…”
Section: Photoacoustic Imagingmentioning
confidence: 99%